The Relationship Between Tax Morale, Tax Fairness, and Tax Complexity on Tax Compliance of MSME Taxpayers in Denpasar City - Anasthasia Regina Sukma; I Ketut Sujana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Taxpayer compliance plays a crucial role in increasing state revenue and supporting national economic development. This study aims to examine the relationship between tax morale, tax fairness, and tax complexity on the compliance of MSME taxpayers in Denpasar City. The research was conducted on MSME taxpayers who are actively registered with the Department of Cooperatives and MSMEs of Denpasar City. A purposive sampling technique was used to select a sample of 100 respondents from a total population of 29,949 MSME taxpayers in Denpasar. The data were analyzed using multiple linear regression. The results indicate that tax morale and tax fairness have a positive and significant relationship with MSME taxpayer compliance in Denpasar City. In contrast, tax complexity shows a negative but statistically insignificant relationship with taxpayer compliance. These findings provide empirical support for the Theory of Planned Behavior and Attribution Theory, highlighting the role of individual attitudes and perceptions in fulfilling tax obligations.